A Review of Successful Construction Project Managers’ Competencies and Leadership Profile - Ali Ghorbani (Journal of Rehabilitation in Civil Engineering, 2023)
The Project Management Institute (PMI) described project management as “Project Management is the application of knowledge, skills, tools, and techniques to project activities to meet the project requirements”. The nature of projects is always dynamic, uncertainty and different from each other. Project lifecycle is along with risk, changes and even sometimes failing happened. Therefore, to bridge these gaps and to achieve the project goal within budget, time, scope and quality. All projects-oriented organizations such as construction firms, consultancy firms, and information and communication technology (ICT) firms, need for trained, competent, leader and experienced project managers. Among the most important elements for a successful project manager, there are combination of knowledge, skill, leadership, ability and personal attitude which are necessary for successful project completion. So, to percept these combinations in detail it is the main purpose of this paper, to review project manager’s competencies and leadership constituents for construction projects throughout lifecycle.